2013
DOI: 10.1111/gwat.12136
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Remediation of Groundwater at Petroleum Sites in California

Abstract: Quantifying the overall progress in remediation of contaminated groundwater has been a significant challenge. We utilized the GeoTracker database to evaluate the progress in groundwater remediation from 2001 to 2011 at over 12,000 sites in California with contaminated groundwater. This paper presents an analysis of analytical results from over 2.1 million groundwater samples representing at least $100 million in laboratory analytical costs. Overall, the evaluation of monitoring data shows a large decrease in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

6
4

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 8 publications
3
41
0
Order By: Relevance
“…Using the Ng model as a foundation, a planning‐level NSZD model can be used to address questions about how long NSZD will take to remove a certain fraction of the LNAPL that was released, and how long it will take to remove a particular constituent down to a particular target level. The inputs to the model would be: (1) current NSZD rate; (2) type of hydrocarbon that was released and the current mass fraction of the various constituent buckets; (3) degradation rates for the lower solubility buckets, as a starting point, can be obtained from Ng et al (), and for soluble components from site‐specific source‐zone groundwater concentration vs. time data (e.g., k source for each BTEX compound [McHugh et al ]); and (4) percentage removal of the bulk LNAPL or of a constituent bucket that would be needed to achieve specific remediation targets (such as a groundwater concentration goal or a LNAPL saturation reduction goal). More work is needed to better understand how to measure and process the proper input data for use in this planning‐level LNAPL remediation timeframe model.…”
Section: Key Learningsmentioning
confidence: 99%
“…Using the Ng model as a foundation, a planning‐level NSZD model can be used to address questions about how long NSZD will take to remove a certain fraction of the LNAPL that was released, and how long it will take to remove a particular constituent down to a particular target level. The inputs to the model would be: (1) current NSZD rate; (2) type of hydrocarbon that was released and the current mass fraction of the various constituent buckets; (3) degradation rates for the lower solubility buckets, as a starting point, can be obtained from Ng et al (), and for soluble components from site‐specific source‐zone groundwater concentration vs. time data (e.g., k source for each BTEX compound [McHugh et al ]); and (4) percentage removal of the bulk LNAPL or of a constituent bucket that would be needed to achieve specific remediation targets (such as a groundwater concentration goal or a LNAPL saturation reduction goal). More work is needed to better understand how to measure and process the proper input data for use in this planning‐level LNAPL remediation timeframe model.…”
Section: Key Learningsmentioning
confidence: 99%
“…Individual studies on plume lengths include 22 to 289 sites per study. Studies on plume stability conditions include 34 to 271 sites per study, with one study addressing the overall plume concentration trends observed at over 4000 UST sites in California (McHugh et al ). Duration of Groundwater Monitoring History . A number of the studies selected sites with longer‐term monitoring periods so as establish plume trends with less uncertainty associated with seasonal fluctuations, sampling variability, and attenuation rates for compounds, such as MTBE, which have been observed to require longer acclimation periods for biodegradation.…”
Section: Compilation Of Data From Published Studiesmentioning
confidence: 99%
“…This approach has proven successful for evaluating long-term monitoring data from multiple sites to provide a more informed basis for understanding typical contaminant trends over time. 25,26 In this study, this type of evaluation was used to quantify attenuation rates and identify factors that influence observed attenuation patterns to better understand how these conditions will dictate the appropriate management strategies.…”
Section: ■ Introductionmentioning
confidence: 99%